Efeitos do exercício sobre o bem-estar no contexto da pandemia do covid-19 - Abreu, Juliana Marques de (2021)
A disease discovered in China, COVID-19, was characterized by the World Health Organization (WHO) as a pandemic in March 2020. Many countries in the world implemented social isolation as a strategy to contain the virus transmission. The samephysical distancing which protects society from COVID-19 from spreading may have an impact on the mental health and well-being of the population This study aims to shed some light on this phenomenon by assessing the relationship between physical activity and SWB among individuals in the social isolation period of COVID-19. Data were collected in Brazil between March 31st and April 2nd, 2020. All volunteers agreed to participate by digitally checking the option of agreement right after reading the Consent Terms. The inclusion criteria were participants over 18 years old who had been in social isolation for at least one week and agreed to the Consent Terms. Three instruments were used: a questionnaire was built for this study which aimed to assess the participants’ exercise routine. The second instrument called Psychosocial Aspects, Wellbeing and Exercise in Confinement (PAWEC) was also created by these researchers and aimed to assess the relationship between well-being and physical activity during the social isolation period. And the third measure was the Brazilian Portuguese-adapted version of the Positive and Negative Affect Schedule (PANAS). A total of 592 participants reported being in social isolation for an average of 14.4 (SD=3.3) days. The amount of participants who reported strength training as exercise increased from 31 (5.2%) before isolation to 82 (13.9%) during quarantine. The study shows that well-being related to the practice of physical activity during quarantine is linked to an established routine of physical activity prior to the social isolation period. Interpretation: People who already practiced physical activity feel more motivated to continue practicing during thisperiod and this causes the appearance of positive affects, unlike people who are only now starting to exercise; according to the study, negative aspects can occur for those who are only just starting. In a period of social isolation, it is important that the practice of physical activity is closer to previous habits, also finding that an obligation to exercise during this period when this was not a reality for the person can contribute to an increase in malaise.